The Political and Technical Aspects of Controlling Inflation - Daniel Gros (Intereconomics, 2023)
After almost four decades of price stability, inflation has recently approached historical highs. Initially driven by global energy and food price increases, the magnitude of the surge in inflation caught central banks and markets by surprise. Price pressures are now increasingly broadening to housing and other services, amplified by wages adjustments. Despite monetary policy tightening, inflation upside risks are large. How can central banks restore control - and with it their own credibility? With the economy weakening and the risk of recession rising, how far should monetary policy tightening go? Featuring contributions from participants in the CEPS 2023 Ideas Lab session on inflation, this Forum examines the options for central banks, the obstacles in their paths and the best course of action.
Keywords: E52; E58; 330; inflation; anti-inflation; central bank; monetary policy; EU countries; Inflation; Inflationsbekämpfung; Zentralbank; Geldpolitik; EU-Staaten; Welt